La villa Arson (1967-1970, arch. : Michel Marot) - Éléonore Marantz (In Situ)
When inaugurated in 1972, the Villa Arson (Nice) embodied an institutional, educational and architectural alternative in the field of artistic education. Initiated locally, the project to build an art school on the heights of Nice had materialized thanks to the decisive support of André Malraux, Minister for Cultural Affairs, and his Director of Architecture, Max Querrien. It had been entrusted to Michel Marot, a young architect who combined the excellence of a brilliant academic curriculum and an undeniable Mediterranean tropism.Michel Marot imagined a powerful architecture, emanating from the place. He imposed a horizontal construction, which slips behind the green curtain of the villa Arson domain. In place of the former gardens landscaped in the 18th and 19th centuries, he deployed an orthogonal maze of concrete and pebble volumes, punctuated by terraces, courtyards and patios, leaving only the colorful mass of the old house to emerge. In this school conceived as a village, which gives a preponderant importance to exhibition and production spaces (workshops), Michel Marot brought architecture into resonance with the primary vocation of the place: allow artists, young artists or confirmed artists, in solitude as in interaction, to build their own creative space.